Relationship Satisfaction and Dyadic Coping in Couples with a Child with Autism Spectrum Disorder - Sim, A.; Cordier, Reinie; Vaz, S.; Parsons, R.; Falkmer, Torbjorn (Springer New York LLC, 2017)
Dyadic coping strategies may play a pivotal role in relationship satisfaction and explain why some couples adapt positively to the challenges associated with raising a child with ASD and others do not. Survey data from 127 caregivers of a child with ASD were used in generalized estimating equation analyses to investigate the factors associated with relationship satisfaction, including socio-demographics, parenting stress and dyadic coping. Results showed that over two-thirds of the sample reported satisfaction, which was associated with low parenting stress, increased use of positive and decreased use of negative dyadic coping strategies. Positive dyadic coping was found to have a greater influence than negative dyadic coping, supporting a strengths-based approach to interventions promoting family resilience.